The substitution of wax with non-wax resist agent for hand drawn batik (extended to screen printing) / Wan Yunus Wan Ahmad, Jamil Salleh and Ponirin Amin - Wan Ahmad, Wan Yunus; Salleh, Jamil; Amin, Ponirin (2006)
Malaysian batiks and wax are co-existing together for a long time. The word batik has come to be used as a generic term, which refers to the process of printing fabric, by using wax as a resist agent that started over 1,500 years ago. Other source claimed that the batik using wax started about 2,500 years ago. The known disadvantages printing using wax are undesirable odour, smoke and unhealthy working environment. The replacement of wax with non-wax physical resist agent reduces the odour and smoke thus produces a safer working environment. The application of the starches based resist agents can be carried out both on canting and hand screen printing techniques. However, canting, the applicator of wax has to be modified to suit to the new kind of resist agents. The resist agents are starches based which are easy to source and inexpensive. In term of design wise, there is no difference with wax based resist agents but the method of canting still need fine tuning to attain the standard of traditional canting design. This is however, very encouraging because it offers alternative to the canting and hand screen printing of batik. Furthermore, the non-wax resist agents can be cured at high temperatures whereas the wax based will melt. The normal fixation methods for batik with wax is immersion in sodium silicate for certain number of hours before washing and followed by boiling to remove wax. By using non-wax resist agents; the choice of fixation is now wider as it can be carried out using traditional sodium silicate, dry heat or steam. On some type of fabrics, soaking and rubbing the starches out in cold water can remove the non-wax resist agents.